Endosomal chloride/proton exchangers need inhibitory TMEM9 β-subunits for regulation and prevention of disease-causing overactivity - Rosa Planells-Cases; Viktoriia Vorobeva; Sumanta Kar; Franziska W. Schmitt; Uwe Schulte; Marina Schrecker; Richard K. Hite; Bernd Fakler; Thomas J. Jentsch (Nature Communications)
Abstract The function of endosomes critically depends on their ion homeostasis. A crucial role of luminal Cl−, in addition to that of H+, is increasingly recognized. Both ions are transported by five distinct endolysosomal CLC chloride/proton exchangers. Dysfunction of each of these transporters entails severe disease. Here we identified TMEM9 and TMEM9B as obligatory β-subunits for endosomal ClC-3, ClC-4, and ClC-5. Mice lacking both β-subunits displayed severely reduced levels of all three CLCs and died embryonically or shortly after birth. TMEM9 proteins regulate trafficking of their partners. Surprisingly, they also strongly inhibit CLC ion transport. Tonic inhibition enables the regulation of CLCs and prevents toxic Cl− accumulation and swelling of endosomes. Inhibition requires a carboxy-terminal TMEM9 domain that interacts with CLCs at multiple sites. Disease-causing CLCN mutations that weaken inhibition by TMEM9 proteins cause a pathogenic gain of ion transport. Our work reveals the need to suppress, in a regulated manner, endolysosomal chloride/proton exchange. Several aspects of endosomal ion transport must be revised.